The Improvement of Childhood Islamic Characters through Cooperative Learning at Lab. School Kindergarten B Faculty of Education, Muhammadiyah University of Jakarta - Farihen, (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to develop Islamic character dimension competences focused on the improvements of Islamic piety, Islamic discipline, and Islamic honesty skills. The findings of the study reveal that childhood Islamic character can improve optimally through cooperative learning. This study employs Kemmis & Taggart action research design, particularly the collaborative action research. The data were collected by using qualitative and quantitative analysis. The qualitative data were analyzed using descriptive analysis, and the quantitative data were analyzed using descriptive statistics. The research concludes that there are some important findings, namely: 1) children’s Islamic moral knowledge competences, (in subdimensions of Islamic moral knowledge skills, Islamic moral reasoning skills, and Islamic moral decision-making skills) are improved through cooperative learning 2) children’s Islamic moral sense competences, (in subdimensions of Islamic moral conscience skills, Islamic self-control skills, and self-esteem skills) have been also developed and 3) Children’s Islamic moral action competences (in subdimensions of moral choice competence in moral situations, Islamic moral value habits, and implantation of Islamic morals, such as politeness, discipline, honesty, and attitude in facing obstacles and temptations). The research findings prove that willingness and habits have developed Islamic character optimally in social life.